Analgosedation in Pediatric Emergency Care: A Comprehensive Scoping Review - Lorenzo Ciavola; Francesco Sogni; Benedetta Mucci; Eleonora Alfieri; Angela Tinella; Elena Mariotti Zani; Susanna Esposito (MDPI AG, 2024)
Effective management of pain and anxiety in pediatric emergency room is crucial for ensuring both the physical and emotional well-being of young patients. Analgosedation, a combination of analgesia and sedation, is commonly used to facilitate various procedures in children. However, selecting the optimal agent and administration route remains challenging due to the unique pharmacological profiles and side effects of available drugs. This scoping review aims to provide a comprehensive analysis of the pharmacological agents used for procedural analgosedation in pediatric emergency settings, focusing on their efficacy, safety, administration routes, and potential side effects. A systematic review of the literature was conducted, focusing on key agents such as ketamine, midazolam, dexmedetomidine, fentanyl, and nitrous oxide. Studies were included based on their relevance to pediatric procedural sedation, particularly in emergency settings. Literature analysis showed that ketamine and fentanyl are effective for managing moderate to severe pain, with a rapid onset of action. Fentanyl is preferred for acute pain management following fractures and burns, while ketamine and midazolam are commonly used for emergency analgosedation. Dexmedetomidine, which induces sedation similar to natural sleep, is particularly effective in preventing pain and agitation during procedures and is well tolerated in children, especially those with developmental disorders. Nitrous oxide, when used in a 50% oxygen mixture, offers a valuable option for conscious sedation during mildly to moderately painful procedures, maintaining respiratory and airway reflexes. No single drug is ideal for all pediatric patients and procedures and the choice of agent should be tailored to the specific clinical scenario, considering both the sensory and affective components of pain. Future research should prioritize large-scale comparative studies, the exploration of combination therapies, and the development of non-pharmacological adjuncts to enhance the safety and efficacy of pediatric analgosedation.